Simultaneous partial monosomy 10p and trisomy 5q in a case of hypoparathyroidism. Issue 8 (August 1992) - Lai, M M; Scriven, P N; Ball, C; Berry, A C
Abstract : We report a case of monosomy for the distal region of the short arm of chromosome 10 (p13----ter) associated with trisomy for the terminal region of the long arm of chromosome 5 (q35.2----ter) that had originated from adjacent 1 segregation of a maternal reciprocal balanced translocation (5;10)(q35.2;p13). We review the clinical findings of previously reported cases of both partial monosomy for 10p and of partial trisomy for 5q, but to our knowledge there are no previous reports of the effects of these two chromosome anomalies together. Clinically our patient showed features typical of partial monosomy for 10p (including hypothyroidism) rather than partial trisomy 5q.